The Effect of Compensation on Turnover Intention with Job Satisfaction and Organizational Commitment as Intervening Variables at Diponegoro National Hospital, Semarang - Haliza Haliza; Andhi Supriyadi; Haniek Listyorini (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of compensation on turnover intention with job satisfaction and organizational commitment as intervening variables. This research was conducted at Rumah Sakit Nasional Diponegoro Semarang with the sample being all hospital nurses. The data analysis technique used is the Structural Equation Modeling (SEM). The results of this study indicate 1. Compensation has a negative and significant effect on turnover intention; 2. Compensation has a positive and significant effect on job satisfaction; 3. Compensation has a positive and significant effect on organizational commitment; 4. Job satisfaction has a negative and significant effect on turnover intention 5. Commitment has a negative and significant effect on turnover intention; 6. Compensation has a negative and significant effect on turnover intention through job satisfaction; 7. Compensation has a negative and significant effect on turnover intention through organizational commitment.